2015
DOI: 10.3390/ijms16011495
|View full text |Cite
|
Sign up to set email alerts
|

Hair Dyes Resorcinol and Lawsone Reduce Production of Melanin in Melanoma Cells by Tyrosinase Activity Inhibition and Decreasing Tyrosinase and Microphthalmia-Associated Transcription Factor (MITF) Expression

Abstract: Hair coloring products are one of the most important cosmetics for modern people; there are three major types of hair dyes, including the temporary, semi-permanent and permanent hair dyes. The selected hair dyes (such as ammonium persulfate, sodium persulfate, resorcinol and lawsone) are the important components for hair coloring products. Therefore, we analyzed the effects of these compounds on melanogenesis in B16-F10 melanoma cells. The results proved that hair dyes resorcinol and lawsone can reduce the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Thus, a modulation of tyrosinase may restore cancer cell sensitivity to chemotherapy by the depletion of pigment amount and increasing the concentration of unbound drug (Buitrago et al 2016). An important point is the fact that TYR expression is observed in nevi and in 80-90% of primary and metastatic melanomas, which makes it a useful diagnostic marker (Pitcovski et al 2017) as well as that decrease of tyrosinase amount is frequently observed and correlates with the MITF level (Hashemi-Shahri et al 2018, Lee et al 2015. In the present study, we observed a significant decrease of tyrosinase in C32 cells after prochlorperazine treatment only in concentration of 3 μM.…”
Section: Discussionsupporting
confidence: 53%
“…Thus, a modulation of tyrosinase may restore cancer cell sensitivity to chemotherapy by the depletion of pigment amount and increasing the concentration of unbound drug (Buitrago et al 2016). An important point is the fact that TYR expression is observed in nevi and in 80-90% of primary and metastatic melanomas, which makes it a useful diagnostic marker (Pitcovski et al 2017) as well as that decrease of tyrosinase amount is frequently observed and correlates with the MITF level (Hashemi-Shahri et al 2018, Lee et al 2015. In the present study, we observed a significant decrease of tyrosinase in C32 cells after prochlorperazine treatment only in concentration of 3 μM.…”
Section: Discussionsupporting
confidence: 53%
“…Resorcinol has been found to have various beneficial properties [12,13,18]. In addition, a recent study reported that resorcinol inhibits melanin biosynthesis [19,20]. However, the detailed mechanisms by which this occurs remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…[76]. The ability of compound 46 to inhibit tyrosinase was credited to its ability to reduce microphthalmia-associated transcription factor (MITF) [77] and tyrosinase mRNA expression as high as 73% and 82%, respectively. The results showed that compound 46 has the potential to be used together with other bioactive ingredients for protection against hyperpigmentation [76].…”
Section: Cinnamic Acid Derivatives With Antioxidant and Anti-inflammamentioning
confidence: 99%